Rehabilitation Following Hand Transplantation. (March 2014) - Bueno, Ericka; Benjamin, Marie-Jose; Sisk, Geoffroy; Sampson, Christian E.; Carty, Matthew; Pribaz, Julian J.; Pomahac, Bohdan; Talbot, Simon G.
Background: Hand allotransplantation can restore motor, sensory and cosmetic functions to upper extremity amputees. Over 70 hand transplant operations have been performed worldwide, but there is little published regarding post-hand transplant rehabilitation. Methods: The Brigham and Women's Hospital (BWH) Hand Transplantation Team's post-hand transplant rehabilitation protocol is presented here. The protocol must be modified to address each transplant recipient's unique needs. It builds on universally used modalities of hand rehabilitation such as splinting, edema and scar management, range of motion exercises, activities of daily living training, electrical stimulation, cognitive training and strengthening. Results: The BWH hand transplant rehabilitation protocol consists of four phases with distinct goals, frequency, and modalities. (1) Pre-operative: functional assessments are completed and goals and expectations of transplantation are established. (2) Initial post-operative (post-operative weeks 1–2): hand protection, minimization of swelling, education, and discharge. (3) Intermediate (post-operative weeks 2–8): therapy aims to prevent and/or decrease scar adhesion, increase tensile strength, flexibility and function, and prevent joint contractures. (4) Late (from 8 weeks forward): maximization of function and strength, and transition to routine activities. The frequency of rehabilitation therapy decreases gradually from the initial to late phases. Conclusions: Rehabilitation therapy after hand transplantation follows a progressive increase in activity in parallel with wound healing and nerve regeneration. Careful documentation of progress and outcomes is essential to demonstrate the utility of interventions and to optimize therapy protocols.